2015
DOI: 10.1160/th14-06-0497
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomes in cardiomyocytes and the peroxisome / peroxisome proliferator-activated receptor-loop

Abstract: SummaryIt is well established that the heart is strongly dependent on fatty acid metabolism. In cardiomyocytes there are two distinct sites for the β-oxidisation of fatty acids: the mitochondrion and the peroxisome. Although the metabolism of these two organelles is believed to be tightly coupled, the nature of this relationship has not been fully investigated. Recent research has established the significant contribution of mitochondrial function to cardiac ATP production under normal and pathological conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 100 publications
(116 reference statements)
2
53
0
Order By: Relevance
“…This fits with the cardio-protective role for peroxisomes first suggested in 1979 by Fahimi where an increase in catalase activity and peroxisome number was reported in heart-tissue of mice fed on an ethanol-rich diet [41]. A recent study added further complexity to this process by proposing a peroxisome/ PPAR-feedback loop to regulate the levels of PPARγ and PPARβ [28]. It was demonstrated that PEX11α deficiency in mouse hearts interferes with the regulation of expression of PPARβ and PPARγ.…”
Section: Other Ppar Family Memberssupporting
confidence: 84%
See 1 more Smart Citation
“…This fits with the cardio-protective role for peroxisomes first suggested in 1979 by Fahimi where an increase in catalase activity and peroxisome number was reported in heart-tissue of mice fed on an ethanol-rich diet [41]. A recent study added further complexity to this process by proposing a peroxisome/ PPAR-feedback loop to regulate the levels of PPARγ and PPARβ [28]. It was demonstrated that PEX11α deficiency in mouse hearts interferes with the regulation of expression of PPARβ and PPARγ.…”
Section: Other Ppar Family Memberssupporting
confidence: 84%
“…The authors suggested that the development of cardiac dysfunction causes disruption of this loop-system, possibly by overload of long chain fatty acids in the system. This theory requires testing by using the PEX11α−/− mouse model with a high fat diet to investigate the risk of mild peroxisomal deficiency in cardiac dysfunction [28].…”
Section: Other Ppar Family Membersmentioning
confidence: 99%
“…A functional PPRE is found about 8.4 kb downstream of the PEX11α promoter (33). Moreover, PEX11α is one of the PEX genes responsible for peroxisome proliferation (33,34). Lack of specific and potent peroxisome proliferators that are independent of PPARs is one of the main technical limitations in distinguishing the beneficial effects of peroxisome proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising therefore that malfunction of peroxisomes leads to peroxisome-specific diseases (Braverman et al, 2013;Weller et al, 2003) and contributes to the pathology of Alzheimer's and Parkinson's diseases, aging, cancer, type 2 diabetes and heart failure (Beach et al, 2012;Colasante et al, 2015;Fransen et al, 2013;Islinger et al, 2012;Trompier et al, 2014). A useful distinction divides peroxisomal diseases into two groups: those in which single enzymatic functions are defective, and those where peroxisome biogenesis is defective per se.…”
Section: Introductionmentioning
confidence: 99%